Pemaknaan Generative AI dalam Pendidikan: Perspektif Sekolah terhadap Penguatan Kewarganegaraan Digital - Dewi Ika Sari; Sukron Mazid; Arif Subowo (Universitas Negeri Semarang, 2026)
The increasing accessibility of Generative Artificial Intelligence (GenAI) tools has driven their exploration and adoption in education. This qualitative research reveals the opportunities and challenges associated with integrating GenAI into education, as well as strategies to encourage teachers and students to use GenAI in the school environment. A survey of 56 Pancasila Education teachers in Magetan Regency at the junior high school level revealed their views on GenAI. Through written reflections, optimistic views about the role of GenAI in education were identified among the teachers, and several strategic ideas were proposed. Thematic analysis revealed three main practices for implementing AI: teaching/learning, administration, and assessment. However, three key challenges were also identified: school readiness, teachers' AI competency, and students' literacy and ethics in AI use. The results indicate that teachers have positive attitudes toward GenAI's potential to improve learning, teaching, and administration, but face obstacles such as limited competency, digital ethical risks, and unequal access to technology. Key findings emphasize the importance of three strategic aspects: teacher capacity building through case-based training, developing ethical guidelines for the use of AI in schools, and providing adequate infrastructure and technical support. The contributions given from the results of this study is to develop an effective strategy to embrace GenAI in Education so that it can encourage the transformation of educational culture that not only prioritizes technological skills, but also instills national character in the digital era.